Ethambutol optic neuropathy - Sudhakar, Padmaja; Acharya, Kishor; Kini, Tonse Ashwini (Frontiers in Neurology, 2025)
Ethambutol is an antitubercular drug that is commonly used in the areas of the world that is endemic to tuberculosis. It is used in infections caused by Mycobacterium tuberculosis and some non-tuberculous infections caused by Mycobacterium species. Ethambutol related toxic optic neuropathy remains one of the most concerning adverse effects of the medication in addition to other non-specific side effects like peripheral neuropathy, nausea, vomiting, joint pain and rash. Recently the guidelines for treatment of tuberculosis in some countries where tuberculosis (TB) is endemic have been revised to allow for fixed dose combinations (wherein a single tablet contains a fixed strength of isoniazid, rifampicin, pyrazinamide, and ethambutol) and longer duration of treatment with ethambutol. Thus, it is anticipated that there will be an increase in ethambutol toxic optic neuropathy. In this minireview we plan to discuss the clinical features, neuro-ophthalmic evaluation, screening and diagnosis of ethambutol toxic optic neuropathy. We will also discuss the available treatment options for this condition.